Literature review : Hyperthermia outcome on intracerebral hemorrhage - Rudi Hariyono (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Hyperthermia occurs in up to 30–40% of patients with ICH and is associated with the highest morbidity and mortality rates. Primary ICH accounts for 85% of all ICH cases and is associated with high morbidity and mortality rates. ICH can lead to primary or secondary brain injury. The purpose of the study was to identify outcome related to hyperthermia on intracerebral haemorraghe. This literature review described four peer-reviewed journals based on inclusion criteria. The results of the analysis of the literature review found that outcome of hyperthermia are mortality and morbidity. Fever can contribute to subsequent brain damage following ICH, hyperthermia to worse outcomes in both ischemic and hemorrhagic stroke patients at 3 months, but the underlying mechanism may differ. Fever is prevalent in people with ICH and is seldom linked with a definite infectious cause